Comparison of pKa values for some phenols imines derived from 3-acetyl and 4-acetyl pyridines. - Adel Azzouz; R Uezbaky (College of Education for Pure Sciences, 2013)
Abstract        The study includes the preparation of a new six imines derived from the mother ketones, namely the 3-acetyl and 4-acetyl pyridines. These imines containing phenols groups in ortho, meta and para positions on aromatic amine side of the molecules. The structures of these compounds were confirmed previously by UV, IR spectra, melting points in addition to the examination of specific chemical tests.         The main object of this study is the determination of pKa values for these phenolic imines and pKa־ for their conjugate acids (nitrilium ions) by potentiometric method. The last as found to be simple, rapid and precise.        Generally, it was observed that, ionization constants values in these acids depend on three main factors :- The chemical structures of imines. The ambient temperature during pKa determination. The type of hydrogen bonding present in these imines.